Configuração espacial e conectividade ecológica: Blumenau (SC) - Edilson Pereira (2024)
This research reflects a growing concern with the need to integrate urban planning and environmental preservation to promote sustainable development and a higher quality of life for urban inhabitants. Additionally, it stands out for its ability to address complex issues such as the inevitable growth of cities and environmental protection. In this context, the study of centralities and nature-based solutions becomes essential for municipal governance, aiming to promote the sustainability of cities. Based on this understanding, the research began by exploring the main concepts related to emerging issues in urban planning, especially environmental ones, as well as seminal concepts about configuration, spatial syntax, and centralities. In this context, the central hypothesis was defined: spatial syntax, when combined with nature-based solutions and centrality metrics, allows for the evaluation of potential centralities and connectivity with the natural environment. This hypothesis unfolds into two: the first focuses on spatial syntax, and the second relates to green areas, as well as floods and landslides. To test these hypotheses, the main objective was to bring the study of centralities closer to the concept of spatial configuration, considering both the configuration of open spaces and barriers as well as the configuration of green areas and their fragments. Subsequently, a method for analyzing and promoting centralities that considers nature-based solutions was proposed. With this purpose, the case study was conducted in the city of Blumenau, chosen for its significant environmental challenges due to its location in a narrow valley, susceptible to floods and landslides. The research explored the use of spatial syntax combined with nature-based solutions to suggest favorable areas for occupation and development in the city. The results indicated that since 2000, urban interventions in Blumenau have altered the city's dynamics, with emphasis on neighborhoods such as Itoupava Norte, Fortaleza, and Velha, which showed high levels of integration, density, and diversity in land use. However, the northern region remains segregated despite development incentives over the past 40 years, which may have been positive in preventing further urban sprawl. Additionally, it was found that, on an urban scale, the green areas in the northern region are larger in size, while the western region presents areas with greater potential for integrating these green spaces. The methodology validated the central hypothesis, demonstrating that spatial syntax combined with nature-based solutions is effective for planning urban centralities, preserving green areas, and mitigating environmental risks. The research offers a valuable tool for urban planners and public managers, suggesting clear guidelines for sustainable urban development with potential applicability in different urban contexts.